Getting the facts, a fieldwork guide for evaluators and policy analysts - Murphy, Jerome T. (Santa Monica, Califonia. : Goodyear Pub. Co., 1980)
This book focuses on approaches for collecting data to be used in policy studies. The chapters move the reader through the various stages of determining appropriate questions for research, developing data through interview, "unobtrusive" observation and document analysis, and, lastly, undertaking qualitative assessments of the data in written reports
Includes index.
Bibliography: p. [201]-213.
lje 17/4/18
Loans
Keywords: Social sciences